Identification of the shared gene signatures between pulmonary fibrosis and pulmonary hypertension using bioinformatics analysis - Zhao, Hui; Wang, Lan; Yan, Yi; Zhao, Qin-Hua; He, Jing; Jiang, Rong; Luo, Ci-Jun; Qiu, Hong-Ling; Miao, Yu-Qing; Gong, Su-Gang; Yuan, Ping; Wu, Wen-Hui (Frontiers in Immunology, 2023)
Pulmonary fibrosis (PF) and pulmonary hypertension (PH) have common pathophysiological features, such as the significant remodeling of pulmonary parenchyma and vascular wall. There is no effective specific drug in clinical treatment for these two diseases, resulting in a worse prognosis and higher mortality. This study aimed to screen the common key genes and immune characteristics of PF and PH by means of bioinformatics to find new common therapeutic targets. Expression profiles are downloaded from the Gene Expression Database. Weighted gene co-expression network analysis is used to identify the co-expression modules related to PF and PH. We used ClueGO software to enrich and analyze the common genes in PF and PH and obtained the PPI network. Then, the differential genes were screened out in another cohort of PF and PH, and the shared genes were crossed. Finally, RT-PCR verification and immune infiltration analysis were performed on the intersection genes. In the result, the positive correlation module with the highest correlation between PF and PH was determined, and it was found that lymphocyte activation is a common feature of the This is a provisional file, not the final typeset article pathophysiology of PF and PH. Eight common characteristic genes (ACTR2, COL5A2, COL6A3, CYSLTR1, IGF1, RSPO3, SCARNA17 and SEL1L) were gained. Immune infiltration showed that compared with the control group, resting CD4 memory T cells were up-regulated in PF and PH.Combining the results of crossing characteristic genes in ImmPort database and RT-PCR, the important gene IGF1 was obtained. Knocking down IGF1 could significantly reduce the proliferation and apoptosis resistance in pulmonary microvascular endothelial cells, pulmonary smooth muscle cells and fibroblasts induced by hypoxia, PDGF-BB and TGF-β1, respectively. Our work identified the common biomarkers of PF and PH and provided a new candidate gene for the potential therapeutic targets of PF and PH in the future.